Does the Hispanic health advantage extend to better management of hypertension? The role of socioeconomic status, sociobehavioral factors, and health care access. (3rd July 2017) - Bacon, Emily; Riosmena, Fernando; Rogers, Richard G.
ABSTRACT: Hispanics in the United States (and foreign-born Hispanics in particular) have relatively favorable health given their lower socioeconomic status compared to, for example, non-Hispanic whites. This phenomenon is often called the Hispanic health paradox (HHP). This study examines whether the previously documented HHP in hypertension prevalence extends to its management using clinical and self-reported measures from the 2007–2012 National Health and Nutrition Examination Surveys. Multivariate models adjusting for demographic, socioeconomic, and sociobehavioral characteristics show an advantage among foreign-born Mexicans in hypertension prevalence relative to non-Hispanic whites (adjusted OR = 0.85). However, compared to non-Hispanic whites, foreign-born Mexicans were 38% less likely to receive treatment recommendations and, when advised to undergo treatment, were 60% less likely to adhere to treatment. Adjusting for health care access and utilization dramatically reduces disparities in hypertension control between foreign-born Mexicans and non-Hispanic whites, suggesting that insufficient systematic access to and use of quality health care erodes the HHP and contributes to the deterioration of health throughout the immigrant experience. Without appropriate interventions, particularly in health care access and utilization, poorer hypertension management among foreign-born Mexicans may negatively affect the Hispanic health profile, increase risk of cardiovascular disease-related mortality, and erode the Hispanic health advantage in the future.